Brazilian method for the development terminological subsets of ICNP®: limits and potentialities - Carina Maris Gaspar Carvalho; Marcia Regina Cubas; Maria Miriam Lima da Nóbrega
ABSTRACT Reflection on the limits and potentialities of a Brazilian method for the development of terminological subsets of ICNP®,(International Classification for Nursing Practice) based on the correlation between this method and international methods. This issue has been debated by the International Council of Nurses (ICN). Although the council propose a guideline for elaboration, they encourage and reinforce the use of various perspectives and processes in the development of subsets. Brazilian Nursing needs to propose a method and deepen reflections on the use of terminological subsets of ICNP® in the reality of the country. The development of subsets in Brazil is considered incipient and the proposed method needs to be used and deepened in order to spread the use of terminology through the application of subsets.